Trans-Inclusive Feminist Praxis: Shifting Religious and Familial Gendered Violence Towards Transgender Acceptance–A USA Case Study - Lockhart, Ezra N. S. (PINS-Psychology in Society, 2024)
Building on the analysis of gender-based violence (GBV) within the lives of black trans women in South Africa, as explored by Shabalala, Boonzaier, and Chirape (2023) in Challenging Ciscentric Feminist Margins, this briefing extends the conversation to the themes of ciscentric oppression, structural violence, and intersectionality in the context of a pilot study I conducted (Lockhart, 2024). The work of Shabalala et al. (2023) calls for intersectional frameworks that challenge cisnormativity, patriarchal violence, and gender performativity—central concepts in understanding the marginalization of trans individuals. Their work powerfully illuminates the ways in which cisgendered and patriarchal norms systematically marginalise trans individuals, particularly trans women of color, through both overt and subtle forms of violence. In a similar vein, my case study of a biracial family in Louisiana, USA, and their 17-year-old trans son, explores how ciscentric gender norms, compounded by religious, racial, and socio-cultural factors, shape the family’s experience of gendered violence and hinder the adolescent’s agency and autonomy, complicating his transition to legal adulthood and his pursuit of self-determination.